Risk Factors for Leptospirosis Infection in Humans and Implications for Public Health Intervention in Indonesia and the Asia-Pacific Region - Sakundarno, M.; Bertolatti, Dean; Maycock, Bruce; Spickett, Jeffery; Dhaliwal, Satvinder (Sage Science Press, 2014)
Prevention and control of leptospirosis require an understanding of risk factors. This review identifies risk factors associated with leptospirosis infection from countries in the Asia-Pacific region, and compares and contrasts these data with those available from Indonesia. MEDLINE, PubMed, and Scopus databases were used to search for relevant articles. Indonesian gray literature was searched for leptospirosis risk factor studies in Indonesia. A total of 34 articles were included in this review. The contrast between peer-reviewed publications and Indonesian gray literature revealed that the variety of risk factors associated with leptospirosis infection is region or area specific. The presence of skin wounds, the existence of rodents, especially rats, and activities related to contact with contaminated surface water are factors frequently reported to have significant association with leptospirosis infection in human in Indonesia and in other Asia-Pacific countries.